Prevalence of Gastro-intestinal Helminthiasis in Cattle of Madi Valley, Chitwan - Bastakoti, R; Paudel, SP; Pandey, A; Acharya, MP (Nepalese Veterinary Journal, 2023)
Cattle is one of the leading species of domestic livestock in Nepal. The helminthic diseases are common in livestock with varied occurrence. This study was carried out to find the prevalence and risk factor associated with gastro-intestinal helminth parasites in 304 fecal samples of cattle of Madi Valley, Chitwan, Nepal. Rectal sample were collected in zip lock plastic bag containing in 10% formalin and preserved in refrigerator before examination. Sedimentation and floatation techniques were used for the detection of helminth parasites. The overall prevalence of gastro-intestinal helminth was found to be 51.32%. The parasitic infection of trematode was 39%, cestode 13% and nematode 48%. In the trematode group, Fasciola sp. 4.61%, Paramphistomum sp. 15.13%, Dicrocoelium sp. 1.64%, Schistosoma sp. 0.66% and Bilharzia sp. 0.99% were prevalent. Among cestode, only Moniezia sp. was observed with infection rate of 7.89%. Nematode included Strongyloides sp. 3.95%, Trichostrongylus sp. 7.24%, Toxocara sp. 3.95%, Oesophagostomum sp. 1.97%, Haemonchus sp. 4.28%, Cooperia sp. 1.97%, Bunostomum sp 0.66%, Nematodirus sp 0.99% and others 3.29%. Mixed infections were observed in 17% of positive samples. Sex and age group showed statistically significant difference. Male have higher prevalence than that of female (P<0.05). Potential risk factor like farmer’s group, water source, body condition score, grazing and rearing system, purpose of animal rearing and last date of drenching showed significant association on prevalence of parasite. Cattle of Madi valley, Chitwan had shown wide range of helminthiasis in cattle.